Impact of COVID-19 on Czech cross-border commuters: Legal perspective - Lukas Novotny (Scientific Papers of the University of Pardubice, Series D: Faculty of Economics and Administration, 2021)
The paper focuses on the impact COVID-19 has on Czech cross-border commuters. Emphasis is placed on the legal and political science perspective and on the comparison of measures against traffic at the state border, against the free movement of persons and specifically against commuter workers (also known as cross-border commuters, or as pendlers in the Czech context), during both previously declared states of emergency in the Czech Republic. From a theoretical perspective, the paper summarizes information and data on cross-border commuters in Europe and the world. The research was performed by means of two qualitative case studies. In general, the legal measures at the Czech-German state border and the conditions of commuter workers during these states of emergency are compared. The research stage also included media searches (during both states of emergency) and content analysis of relevant policy outputs. The results suggest that border closures and related measures and the inability to travel abroad were unconstitutional, which also damaged commuters. And this also resulted in the fact that during the second state of emergency, the commuters were, in effect, not subject to any measures from the Czech side.
Keywords: O52; R58; J6; K31; 330; Borderland; Cross-Border Commuting; Covid-19; Labour Market; Czech Republic; Germany